Zastosowanie metody autoregresji w prognozowaniu cen akcji firmy telekomunikacyjnej - Przybylska-Mazur, Agnieszka (Aplication of the Autoregression Method in Prediction of the Stock Prices of Telecommunication Firm, 2006)
Many commodity prices, the exchange rates and the securities prices are submitted to influence of fate. In this article was presented one of the stochastic method of prediction - the autoregression method. This method was applied on the prediction of stock price of TP S.A. The autoregression method is used for prediction of one-dimensional stationary time series. So in this article was applied the test verifies the order of integration of time series.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 274-285